Selection bias in innovation studies: A simple test - Gaétan De Rassenfosse; Annelies Wastyn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The study of the innovative output of firms often relies on a count of patents filed at one single office of reference such as the European Patent Office (EPO). Yet, not all firms file their patents at the EPO, raising the specter of a selection bias. Using a novel dataset of the whole population of patents by Belgian firms, we show that the single-office count results in a selection bias that affects econometric estimates of innovation production functions. We propose a methodology to evaluate whether estimates that rely on the single-office count are affected by a selection bias.
Keywords: O31; C18; C52; C81; 330; Innovation production function; patent; R&D; selection bias